Analisis Penerapan Kurikulum Merdeka: Kajian Buku Tema Cemerlang Bagian Materi Bahasa Indonesia Kelas II SD/MI - Dewi, Nadila Putri Kumala; Siregar, Bulan An Nur; Sundari, Sundari; Mukhlis, Muhammad (UIR Press, 2025)
This study aims to describe the analysis of the implementation of the Merdeka curriculum in the Cemerlang thematic book for the Indonesian language section for grade II elementary school from Usaha Makmur Solo Publisher. This study refers to the textbook assessment standards from the Education Standards, Curriculum, and Assessment Agency in 2022 which has set several criteria for assessing textbooks. The assessment aspects include 4 things, namely material standards, presentation standards, design standards, and graphic standards. This study uses a qualitative research type, with a content analysis method. The data collection technique in this study was through documentation. The data analysis technique in this study was by processing and analyzing the data that had been collected. The results of the study show that the Cemerlang thematic book for the Indonesian language section for grade II elementary school from Usaha Makmur Solo Publisher is included in the good category because it includes the use of attractive visuals, good material presentation and in accordance with the curriculum, involving technology with the presence of QR codes that can be used by students and teachers to support learning in class or at home.